دراسة مكونات الزيت العطري لأوراق نبات الريحان (الحبق) وفعاليتها المضادة للجراثيم - الحداد عماد (Latakia University Journal -Medical Sciences Series, 2017)
تم جمع المجموع الخضري لنبات الريحان من منطقة مشتى الحلو من شهرتشرين الأول لعام 2014, وجرى استخلاص الزيت العطري بطريقة النقع بالهكسان النظامي وبطريقة الجرف ببخار الماء, وتبين أن نسبة الزيت العطري يساوي 2,7% من وزن العينة الأولى, و2,5% من وزن العينة الثانية, تم تحديد التركيب الكيميائي للزيت العطري بالتحليل باستخدام جهاز الGC/MS وباختيار شروط فصل مناسبة. التحليل سمح بتحديد 18 مركباً للعينة المستخلصة بالنقع بالهكسان النظامي و11 مركباً بطريقة الجرف ببخار الماء,وهذه المركبات في العينة الأولى هي: المركبات التربينية وهي ستة مركبات تشكل نسبة 21,22% من وزن الزيت العطري, المركبات الهيدروكربونية وهي سبعة وتشكل نسبة 21,81% , ويوجد مركب كيتوني ونسبته 2,32%, ومركبين ذو طبيعة استرية بنسبة 18,96%, ومادة فينولية نسبتها 21,6% ومركب إيتيري بنسبة 14,8%.أما بالنسبة لمركبات العينة الثانية فهي: الألكانات الهيدروكربونية وهي ستة بنسبة 91,24% من وزن الزيت العطري, ثلاث مركبات تربينية بنسبة 3,17%, مادة فينولية بنسبة 3,96%, ومركب ايتيري بنسبة 1,62%.كما تبين أن للزيت العطري المستخلص تأثيراً مثبطاً لنمو الجراثيم العنقودية المذهبة بشكل أكبر من التأثير المثبط للعصيات القولونية. In October 2014, the collected air-green samples of Basil herb were gathered from the region of MashtaAlhulu in the ,Then the volatile oil from fresh samples was extracted with N-Hexane and other samples with steam distilled water, and we have found the percentage of the volatile oil in the first sample (N-Hexane) is 2,7% , and 2,5% in the second sample (steam distilled water). Suitable conditions were chosen to separate the components of the volatile oil by GC-MS and we noticed : - the first sample (extracted with N-hexane) contain 18 compounds, and they are: Six Terpenes compounds and they form 21.22%,Hydrocarbon compounds form 21.8% from the total weight and they are 7 compounds, and one compound from Ketone class dicycle and its percentage is 2.32%,and two Ester compound and they form 18.96%, One phenolic compound and forms 21.60%, one Ether compound and forms 14.08%. -the volatile oil from the second sample (extracted with steam distilled water) contains 11 compounds, and they are: 6 compounds belong to Hydrocarbon class and they are the main components in the volatile oil with a 91.24% of the oil total weight, One compoundfrom Ether class forms 1.62%, one phenolic compound which forms 3.93%, and three Terpenes compounds and they form 3.17%.